Dampak Implementasi Manajemen Berbasis Sekolah Terhadap Prestasi Akademik Di UPT SPF SMP Negeri 22 Kota Makassar - Indriati Amirullah; Musfirah Musfirah (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to evaluate the impact of implementing School Based Management (MBS) on student academic achievement at UPT SPF SMP Negeri 22 Makassar City. Using qualitative research methods, this study collects data through interviews, observations and document analysis. The research results show that the implementation of SBM has had a positive impact on student academic achievement. Innovation in the teaching and learning process, increased involvement of parents and the community, as well as increased school autonomy and accountability are some of the factors that have contributed to this increase in academic achievement. However, this research also identified several challenges in implementing SBM, such as the need for greater training and support for teachers and school staff. This research suggests that further efforts are needed to overcome these challenges and maximize the benefits of SBM.